(untitled) (Pesquisa Brasileira em Ciência da Informação e Biblioteconomia, 2020)
Abstract: Teaching information literacy is a new important issue, which has received lots of attention from most organizations and different institutions of Iran. Public libraries in different countries of the world have also paid attention to this important issue. The aim of this research is to teach information literacy to 11-16-year-old teenage members of public libraries of Tehran 1st region. This is a descriptive study conducted using survey method. The statistical population of the research consisted of teenage members (11-16 years old) of Shahid Bahonar public library, who are more than 500 individuals. Using Morgan table, research sample size was calculated to be 217. Data were collected using researcher-made questionnaire. The collected data were analyzed by descriptive and inferential statistics. Research findings showed that the information literacy skills of 11-16-year-old teenage members of public libraries of Tehran 1st region (3.38) are higher than average (3) and the role of information literacy in teaching information literacy to teenagers (2.5) is lower than average (3). Keywords: Public libraries. Information literacy. Teaching information literacy. Lifelong learning. Link: https://periodicos.ufpb.br/ojs/index.php/pbcib/submission/wizard/2?submissionId=55335#step-2